2019
DOI: 10.1590/0102-33062018abb0236
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal communities in soils under three phytophysiognomies of the Brazilian Atlantic Forest

Abstract: Arbuscular mycorrhizal fungi (AMF) play an important role in plant community productivity and structure, and so studying the factors that affect the diversity and structure of this fungal community is important for understanding their ecology in tropical forests. We investigated AMF spore communities and root colonization under three forest phytophysiognomies (Restinga Forest, REF; Lowland Ombrophilous Dense Forest, LLF; and Montane Ombrophilous Dense Forest, MTF). Spore abundance was lowest in LLF and highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Although many researchers have reported that soil impacts AMF diversity, there is no consistent conclusion. Some authors have reported that soil texture has a more significant influence on the AMF community than soil chemical properties (Da Silva et al 2015, Duarte et al 2019. However, other studies have found that while soil chemistry does modify the AMF community, soil texture does not appear to do so (Pagano et al 2013).…”
Section: Soil Characteristics Driving Am Fungal Communitiesmentioning
confidence: 99%
“…Although many researchers have reported that soil impacts AMF diversity, there is no consistent conclusion. Some authors have reported that soil texture has a more significant influence on the AMF community than soil chemical properties (Da Silva et al 2015, Duarte et al 2019. However, other studies have found that while soil chemistry does modify the AMF community, soil texture does not appear to do so (Pagano et al 2013).…”
Section: Soil Characteristics Driving Am Fungal Communitiesmentioning
confidence: 99%
“…To ascertain the discrepancies in AMF communities among these forests, the researchers evaluated spore abundance, diversity indices, and root colonization rates. The study findings showed that spore abundance was at its minimum in LLF and maximum in REF, with no significant variations compared to MTF [31]. This indicates that the abundance of AMF spores is shaped by the particular traits of individual forest types (Table 1).…”
Section: Literature From Previous Studies 21 Effect Of Deforestation ...mentioning
confidence: 81%
“…Arbuscular mycorrhizal fungi have also shown differences in colonization rates among the same host plants across a gradient from coastal to inland habitats (Guillén et al, 2019). However, Duarte et al (2019) saw no significant difference in PRLC in similar plant communities among three distinct forest types—from lowland to montane. Combined with our results, these studies suggest that PRLC can be affected by various factors including climate, edaphic conditions, and habitat type.…”
Section: Discussionmentioning
confidence: 94%